IMPROVING WRITING ABILITY THROUGH COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) - Srikandini Narulita; Samsu Armadi (Kantor Bahasa Kalimantan Timur, 2023)
AbstractThe study is aimed at improving the students’ writing ability in writing using Group Discussion and Cooperative Integrated Reading and Composition (CIRC) models of Cooperative Learning Strategy. The study employs Collaborative Classroom Action Research design. The subjects of the study are 5 students of fourth semester of the English Department of Kutai Kartanegara University in 2021-2022. The result of this study shows that Cooperative Learning strategy with Group Discussion and Cooperative Integrated Reading and Composition (CIRC) models is effective in improving the students’ writing ability. In the pretest, the average score of the students’ writing achievement was 4.15 on a 1.00 to 6.00 scale. Five students obtained a ‘poor’ level. After Cooperative Learning strategy was implemented, the average score of the class in Cycle 1 increased slightly to 4.65. In Cycle 2, the average score of the class increased to 5.04, and all subjects achieved the criteria of success. Keywords: writing ability, cooperative learning, strategy Abstrak Penelitian ini bertujuan untuk meningkatkan kemampuan menulis mahasiswa dalam menulis Bahasa Inggris dengan menggunakan model strategi pembelajaran Cooperatif Group Discussion dan Cooperative Integrated Reading and Composition. Peneliti menggunakan desain Penelitian Tindakan Kelas Kolaboratif dan subjek penelitian adalah 5 mahasiswa semester 4 Prodi pendidikan Bahasa Inggris Universitas Kutai Kartanegara tahun ajaran 2021-2022. Hasil penelitian ini menunjukkan bahwa strategi Cooperative Learning dengan model Group Discussion dan Cooperative Integrated Reading and Composition (CIRC) efektif dalam meningkatkan kemampuan menulis siswa. Pretest sebelum penerapan strategi ini, nilai rata-rata prestasi menulis siswa adalah 4,15 pada skala 1,00 sampai 6,00. Lima siswa memperoleh tingkat 'buruk'. Setelah penerapan strategi Cooperative Learning, nilai rata-rata kelas pada Siklus 1 meningkat tipis menjadi 4,65. Hanya 2 mahasiswa yang tidak mencapai kriteria keberhasilan. Siklus 2 nilai rata-rata kelas meningkat menjadi 5,04 dan semua subjek mencapai kriteria keberhasilan. Mahasiswa terlibat aktif dan sangat termotivasi untuk mengikuti kelas menulis dengan sistem ini. Kata-kata kunci: kemampuan menulis, pembelajaran kooperatif, strategi